Pengaruh Media Diorama Berbasis STEM terhadap Hasil Belajar IPAS Siswa Kelas VI SD Inpres Kuanino 3 - Elis Belya Dami; Roswita Lioba Nahak; Heryon Bernard Mbuik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Dami, Elis Belya. 2025. The Effect of STEM-Based Diorama Media on the IPAS Learning Outcomes of Sixth-Grade Students at SD Inpres Kuanino 3. Undergraduate Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Citra Bangsa. Advisor I: Roswita Lioba Nahak, S.Pd., M.Pd. Advisor II: Heryon Bernard Mbuik, S.PAK., M.Pd. This study was backgrounded by the low IPAS learning outcomes at SD Inpres Kuanino 3 due to teacher-centered instruction and the lack of contextual media, making the eclipse topic difficult for students to understand. The purpose of this research was to determine the effect of STEM-based diorama media on sixth-grade students’ IPAS learning outcomes and to provide an innovative learning alternative. This research employed a quasi-experimental method with a Nonequivalent Control Group Design involving all 40 students (20 experimental, 20 control). The instrument was a 20-item multiple-choice test validated with Pearson Product Moment (all items valid, rcount > rtable 0.312) and reliability tested with the Spearman–Brown method (r11 = 0.777, high category). Item analysis showed 14 questions of moderate difficulty and 6 easy questions, with discrimination indices ranging from sufficient to very good. Data were analyzed using descriptive and inferential statistics. Prerequisite tests included Shapiro–Wilk normality (sig. > 0.05) and Levene’s homogeneity (sig. > 0.05), indicating normal and homogeneous data. Hypothesis testing using a paired-sample t-test produced sig. 0.000 < 0.05, thus rejecting H₀. The average pretest score of 49,25 increased to 87,25 on the posttest. These results demonstrate that STEM-based diorama media is valid, reliable, practical, and effective in improving elementary students’ IPAS learning outcomes.